2001
DOI: 10.2527/2001.7992268x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybrid, maturity, and mechanical processing of corn silage on intake and digestibility by beef cattle.

Abstract: A study involving a 2 x 2 x 2 factorial arrangement of treatments was conducted to evaluate effects of hybrid (Pioneer 3335 and 3489), maturity (half milkline and blacklayer), and mechanical processing (field chopper with and without on-board rollers engaged) on intake and digestibility of corn silage. Forty Angus steers (322 +/- 5.2 kg BW) were assigned to the eight silage treatments (five steers per treatment) and individually fed using electronic gates. Diets consisted of 60% corn silage and 40% chopped alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
59
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 29 publications
(37 reference statements)
15
59
1
7
Order By: Relevance
“…Furthermore, Andrae et al (2001) and Kramer-Schmid et al (2016) noted that starch content in maize silage is not a good predictor of either aNDFD or OMD, which was the case also in our research (r = −0.17, r = −0.13, respectively). Therefore, it cannot be excluded that beside aNDF digestibility also one or more of these correlated factors have been responsible for the cow's production responses.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, Andrae et al (2001) and Kramer-Schmid et al (2016) noted that starch content in maize silage is not a good predictor of either aNDFD or OMD, which was the case also in our research (r = −0.17, r = −0.13, respectively). Therefore, it cannot be excluded that beside aNDF digestibility also one or more of these correlated factors have been responsible for the cow's production responses.…”
Section: Resultssupporting
confidence: 56%
“…Within the same maize genotype, a decreasing aNDF con- (Jensen et al 2005). Similarly, Andrae et al (2001) found that the aNDF content of maize silage was poorly correlated with aNDFD.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Fonte: Elaboração dos autores. Andrae et al (2001), quando avaliando a degradabilidade in situ de silagens de milho, concluíram que o efeito combinado da colheita da lavoura de milho em dois estádios (meia linha do leite e grão cheio) juntamente com a utilização de rolos para quebra dos grãos, resultaram em uma tendência (P<0,10) de maior desaparecimento da matéria seca potencialmente degradável, quando comparado com a não utilização dos rolos na colhedora de forragem.…”
Section: Resultados E Discussõesunclassified
“…While grains are highly digested (Andrae et al, 2001) the green part of the plant (stover) seems to be of limited digestibility. Leaf and stem tissues are hard to digest because of the complex structure of their cell walls (Buxton and Redfearn, 1997).…”
Section: Introductionmentioning
confidence: 99%